Hypersensitivity reactions to human papillomavirus vaccine in Australian schoolgirls: retrospective cohort study. (2nd December 2008) - Kang, Liew Woei; Crawford, Nigel; Tang, Mimi L K; Buttery, Jim; Royle, Jenny; Gold, Michael; Ziegler, Christine; Quinn, Patrick; Elia, Sonja; Choo, Sharon
Abstract : Objective To describe the outcomes of clinical evaluation, skin testing, and vaccine challenge in adolescent schoolgirls with suspected hypersensitivity to the quadrivalent human papillomavirus vaccine introduced in Australian schools in 2007. Design Retrospective cohort study. Setting Two tertiary paediatric allergy centres in Victoria and South Australia, Australia. Participants 35 schoolgirls aged 12 to 18.9 years with suspected hypersensitivity reactions to the quadrivalent human papillomavirus vaccine. Main outcome measures Clinical review and skin prick and intradermal testing with the quadrivalent vaccine and subsequent challenge with the vaccine. Results 35 schoolgirls with suspected hypersensitivity to the quadrivalent human papillomavirus vaccine were notified to the specialised immunisation services in 2007, after more than 380 000 doses had been administered in schools. Of these 35 schoolgirls, 25 agreed to further evaluation. Twenty three (92%) experienced reactions after the first dose. Thirteen (52%) experienced urticaria or angio-oedema, and of these, two experienced anaphylaxis. Thirteen had generalised rash, one with angio-oedema. The median time to reaction was 90 minutes. Nineteen (76%) underwent skin testing with the quadrivalent vaccine: all were skin prick test negative and one was intradermal test positive. Eighteen (72%) were subsequently challenged with the quadrivalent vaccine and three (12%) elected to receive the bivalent vaccine. Seventeen tolerated the challenge and one reported limited urticaria four hours after the vaccine had been administered. Only three of the 25 schoolgirls were found to have probable hypersensitivity to the quadrivalent vaccine. Conclusion True hypersensitivity to the quadrivalent human papillomavirus vaccine in Australian schoolgirls was uncommon and most tolerated subsequent doses.